Advancing Sustainable Irrigation Practices through Innovative Malt Barley Technologies: A Case Study at Barneb Irrigation, South Wollo, Legambo District, Ethiopia - Abate, Sisay Dessale; Tilahun, Gebeyaw; Mihret, Tewabe; Biyazen, Brihanu; Feyisa, Tesfaye; Yitayew, Asresu; Gebru, Akalu; Getachew, Getachew; Andre Van Rooyen, Andre (International Journal on Food, Agriculture and Natural Resources, 2025)
Pre-scale up study was conducted to promote Malt Barley improved irrigation technologies for enhancing water use efficiency, farm productivity, and the benefits of smallholder farmers at Barneb small-scale irrigation scheme. The rationality was that improved irrigation method is preferable for water saving, increasing yield, decreasing water logging and soil erosion, enhancing water productivity and easily for water application than the traditional flooding method. In order to achieve these objective farmers research was established with 30 (26 male and 4 female household heads) members. The fertilizer was applied as 100 kg ha-1 Urea and 100 kg ha-1 NPS rate. Double row raised bed furrow technology with 40 cm bed width, 20 cm furrow width, and 20 cm row spacing were applied. The net irrigation applied depths were 19 mm for initial stage and 44.3 mm for mid-season stage with 30-days irrigation interval. The result shows that the application of improved seed with improved management practices had nearly doubled water productivity (4.7 kg m-3) over the farmer's practice (2.4) kg m-3). Therefore, Ministry of Agriculture in collaboration with non-government organizations and other private sectors should work to scaling the technologies through irrigation extension packaging system. Keywords: FRG, Farmers practices, Improved practices, Small-scale irrigation, Scaling